Regulation of Hippo, TGFβ/SMAD, Wnt/β-Catenin, JAK/STAT, and NOTCH by Long Non-Coding RNAs in Pancreatic Cancer - Farooqi, Ammad Ahmad; Nayyab, Sawera; Martinelli, Chiara; Berardi, Rossana; Katifelis, Hector; Gazouli, Maria; Cho, William C. (Frontiers in Oncology, 2021)
Rapidly evolving and ever-increasing knowledge of the molecular pathophysiology of pancreatic cancer has leveraged our understanding altogether to a next level. As compared to the exciting ground-breaking discoveries related to underlying mechanisms of pancreatic cancer onset and progression, there had been relatively few advances in the therapeutic options available for the treatment. Since the discovery of the DNA structure as a helix which replicates semi-conservatively to pass the genetic material to the progeny, there has been conceptual refinement and continuous addition of missing pieces to complete the landscape of molecular biology. Starting from transcription to translation, modern era has witnessed non-coding RNA discovery and central role of these versatile regulators in onset and progression of pancreatic cancer. Long non-coding RNAs have been shown to act as competitive endogenous RNAs (ceRNAs) through sequestration and competitive binding to myriad of miRNAs in different cancers. In this review we will set spotlight on emerging evidence of regulation of different signaling pathways (Hippo, TGF/SMAD, Wnt/β-Catenin, JAK/STAT and NOTCH) by lncRNAs. Conceptual refinements have enabled us to understand how lncRNAs play central role in post-translational modifications of various proteins and how lncRNAs work with epigenetic-associated machinery to transcriptionally regulate gene network in pancreatic cancer.